2015
DOI: 10.1111/bjh.13330
|View full text |Cite
|
Sign up to set email alerts
|

United Kingdom immune thrombocytopenia registry: retrospective evaluation of bone marrow fibrosis in adult patients with primary immune thrombocytopenia and correlation with clinical findings

Abstract: Summary Fibrosis has been reported in some patients with immune thrombocytopenia (ITP) treated with thrombopoietin receptor agonists (TPO‐RA). However, fibrosis has also been reported in patients with various stages of ITP, who were TPO‐RA treatment‐naïve. In our study, we looked for fibrosis in bone marrow trephine biopsies taken at initial diagnosis from 32 adult patients with ITP. Ten of the 32 evaluated samples (31·25%) showed increased reticulin (Grade 1–2 on Bauermeister scale and Grade 0–1 on the Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Whether the risk of BM fibrosis is due to the TPO-RAs themselves or the underlying disease remains unclear. Even in the absence of TPO-RAs, the results of several studies have revealed the presence of background BM reticulin fibrosis in patients with a diagnosis of ITP [6,11,18,19,20]. Furthermore, increased BM reticulin formation has been described in patients with refractory ITP, as well as in those with other autoimmune diseases [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the risk of BM fibrosis is due to the TPO-RAs themselves or the underlying disease remains unclear. Even in the absence of TPO-RAs, the results of several studies have revealed the presence of background BM reticulin fibrosis in patients with a diagnosis of ITP [6,11,18,19,20]. Furthermore, increased BM reticulin formation has been described in patients with refractory ITP, as well as in those with other autoimmune diseases [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Mild reticulin has been shown to be present in the bone marrow (BM) of approximately 27-31% of hematologically normal patients [3,4] and 28-52% of patients diagnosed with primary ITP [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, a history of thrombosis does not definitely contraindicate TPO-RAs if the platelet count is sufficient to maintain antiplatelet or anticoagulation therapy. Some questions remain about the long-term safety and potential risk of reticulin deposits within the bone marrow with TPO-RAs, but reassuring data have been reported Rizvi et al, 2015). To our knowledge, there are no data to show that reticulin deposits increase with age.…”
Section: Thrombopoietin-receptor Agonists (Tpo-ras)mentioning
confidence: 96%
“…Moreover, an indirect comparison between patients who received TPOs for 24-26 weeks has demonstrated an overall durable response rate of 42% for eltrombopag and 49% for romiplostim [25]. More importantly, the increase of bone marrow fibrosis appears to be higher (20-31%) than has been suggested [26,27]. …”
Section: Discussionmentioning
confidence: 99%